Dislipidemia dan Oval Fat Bodies Dalam Urin - Indranila Indranila (MEDIA MEDIKA INDONESIANA, 2008)
Dyslipidemia and oval fat bodies in urineBackground: Lipid profiles such as cholesterol, triglyceride, HDL-cholesterol and LDL-cholesterol screening are expensive. Oval fat bodies (OFB) an epithelial tubulus cell within lipid degenerated/macrophag contains fat granule, is a marker of lipiduria will be expected as a feature of serum lipids and may be performed as a simple non invasive, inexpensive laboratory test. The aim of the study was to analyze the correlation between dyslipidemia and OFB.Methods: This study was performed in 66 male and female subjects of hypercholesterolemia and hypertriglyceridemia of 20-83 years old, which come to a private laboratory in Semarang within 3 months. Sample were taken purposively. The method used in detecting lipids serum was enzymatics (CHOD-PAP for cholesterol and GPO enzymatic for triglyceride) and OFB examination in urine using Sternheimer–Malbin staining.Results: Triglyceride and cholesterol mean value were 210.8 mg/dl (±131.74) and 230.6 mg/dl (±36.4). OFB were found in the urine of on 15 subjects (75%) with hyperlipidemia, 26 subjects (72.2%) with hypercholesterolemia and 6 subjects (70%) with hypertriglyceridemia. There were corellations between hypercholesterolemia and hypertriglyceridemia and OFB (r1=0.82, p1=0.01; r2=0.84, p2=0.05; r3=0.75, p3=0.05).Conclusions: There are positive correlation between dyslipidemia and the presence of OFB in urine.Keywords: Dyslipidemia, oval fat bodies.ABSTRAKLatar belakang: Profil lipid sebagai uji saring umumnya adalah kolesterol, trigliserid, kolesterol-HDL, kolesterol-LDL dimana biaya pemeriksaan ini masih cukup mahal, sementara pola makan cenderung tinggi lemak. Oval fat bodies (OFB) merupakan salah satu petanda lipiduria diharapkan dapat menggambarkan keadaan lemak darah pada uji saring laboratorium secara sederhana, non invasif dan murah. Penelitian ini bertujuan untuk mengetahui hubungan antara dislipidemi dengan OFB.Metode: Pengamatan dilakukan pada 66 subyek usia dewasa baik laki-laki dan wanita dengan hiperkolesterolemia dan atau hipertrigliseridemia yang memeriksakan diri di laboratorium klinik swasta di Semarang selama kurun waktu 3 bulan secara purposivesampling. Metode pemeriksaan yang digunakan adalah ensimatik (CHOD–PAP untuk kolesterol dan GPO ensimatik untuk trigliserida) dan mikroskopik sedimen urin menggunakan pengecatan Sternheimer-Malbin untuk OFB.Hasil: Didapatkan rerata trigliserid dan kolesterol 210,8 mg/dl (±131,7) dan 230,6 mg/dl (±36,4) OFB ditemukan dalam urin 15 subyek (75%) dengan hiperlipidemia, 26 subyek (72,2%) dengan hiperkolesterolemia dan 6 subyek (70%) dengan hipertrigliseridemia. Ada korelasi antara hiperlipidemia, hiperkolesterolemia dan hipertrigliseridemia dengan keberadaan OFB di urin (r1=0,82, p1=0,01; r2=0,84, p2=0,05; r3=0,75, p3=0,05).Simpulan: Ada korelasi positif antara dislipidemia dengan ditemukannya OFB di urin.